2000
DOI: 10.1080/02673030050134556
|View full text |Cite
|
Sign up to set email alerts
|

The Line of Descent in the Intergenerational Transmission of Domestic Property

Abstract: Although there has been a growing interest over recent years in the intergenerational transmission of Western domestic property, and speci cally housing inheritance, the line of descent in this transmission has been ignored. We do not know whether domestic property goes disproportionately to the next generations(s) of men, or to women, or equally to men and women as the Western cognatic system of descent would dictate. This paper explores the line of descent through an argument proffered by two European sociol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Eight (23.5 percent) testaments bequeathed to a mix of males and females and eight (23.5 percent) bequeathed to nonkin or the church. These findings are consistent with those of Mullins 33 who found that females (daughters) were more likely to inherit domestic property such as houses. However, in this situation it was sisters (5) and nieces (5) who inherited a whole estate; the other beneficiaries were nephews and brothers.…”
Section: Making Comparisons-domestic Bequests 1951 and 2000supporting
confidence: 91%
See 3 more Smart Citations
“…Eight (23.5 percent) testaments bequeathed to a mix of males and females and eight (23.5 percent) bequeathed to nonkin or the church. These findings are consistent with those of Mullins 33 who found that females (daughters) were more likely to inherit domestic property such as houses. However, in this situation it was sisters (5) and nieces (5) who inherited a whole estate; the other beneficiaries were nephews and brothers.…”
Section: Making Comparisons-domestic Bequests 1951 and 2000supporting
confidence: 91%
“…In English society Finch et al found that single women are more likely to exercise testamentary freedom by bequeathing their property to their friends. 19 Mullins 20 questioned the claim of French feminists Delphy and Leonard 21 who argued that property goes disproportionately to the next generation of men because of the power of patriarchy. He suggested that they did not provide enough empirical evidence to support this claim and argued that they failed to differentiate between domestic and market property.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Birth order, age and gender are also considered to be powerful structuring influences on sibling relationships, with siblings' behaviours or those of family members' towards them often interpreted in light of these influences (Edwards et al, 2005). In relation to transfers of wealth, practices based on the principles of primogeniture (the right of inheritance of the firstborn son, informed either by law or custom) provide an extreme case, with more gender-neutral patterns of inheritance emerging in countries such as Australia (Mullins, 2000). Pillimer et al (2012) also highlight the potential influence of gender on inter-family relationships, noting that fathers report lower levels of ambivalence towards daughters, whilst mothers report lower levels towards sons.…”
Section: Structured Ambivalence and Sibling Relationshipsmentioning
confidence: 99%